Temporal change in species and functional plant traits in the moist grassland on the Sete Cidades National Park, Piauí, Brazil - MRA Mendes; MC Silva Júnior; AAJF Castro; FSC Takahashi; CBR Munhoz (Brazilian Journal of Biology)
The present study investigated the dynamic on a short-time scale in the vegetation in moist grassland of the Sete Cidades National Park, Piauí. Herb-subshrub layer samples was carried out in July 2007, 2009 and 2011. Changes in structural, floristic and functional traits in the community were assessed by species richness, diversity and similarity indices between those periods, as well as by hierarchical classification and ordination. Cluster and Principal Component Analyses identified functional groups according to 23 species trait state. To distinguish the contribution of space and time configuration in the community structure, we used the variance partition technique. The functional groups of chamaephytes and therophytes II were associated with wetter sites, while the groups of non-tussock hemicriptophytes I, tussock hemicriptophytes (FG4), and geophytes (FG5) were associated to the drier ones. We found a non-accelerated dynamics, at least on a short-time scale, represented by some descriptors in the community, such as the close similarity between the inventories and ordering of sampling transects in moist grassland. Therefore, besides considering the partition of the temporal niche as a mechanism for the co-existence of species, the heterogeneity of space dictated by environmental filters seems to determine the stability of the this grassland communities over time.